ILLEGAL URBAN ENTREPRENEURSHIP? THE CASE OF STREET VENDORS IN LAGOS, NIGERIA - Taibat Lawanson (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
This paper considers the vulnerabilities experienced in making a living as a street trader in Lagos, Nigeria. Using the Tejuosho - Yaba - Ojuelegba - Barracks quadrant as a case study, the paper investigates the socio-economic profile of street traders, their basic survival strategies and goes further to examine the interface between street vendors and related urban stakeholders. Relying on both qualitative (informed participant interviews) and quantitative (survey by purposive sampling) data analysis, the study revealed that most of the respondents were aged between 16 and 35 years old and operated subsistence enterprises which were begun due to unemployment and the high cost of the renting stalls at the nearby Yaba market. The major challenge experienced was the institutionalized harassment by KAI officials, which aided extortion by other local stakeholders. The paper concludes by highlighting the potentials of the informal economic sector and the strategic role it plays in the emerging African city form.